WLS Penimbang Kaplan Meier untuk Estimasi Model Regresi Linear Data Tersensor Kanan - Anisa Dwi Rahmadani; Abdul Kudus (Bandung Conference Series: Statistics, 2022)
Abstract. The method for estimating parameters in linear regression is to use Ordinary Least Square (OLS). But the use of linear regression is limited when the independent variables are continuous and the entire data set is complete observed data. Therefore, it is not appropriate to examine phenomena that contain censored data. In the case of dependent variables with censored data, the Weighted Least Square method with Kaplan Meier weighing and Synthetic Data Transformation is a solution to estimate linear regression parameters. This article will discuss the Weighted Least Square method with the Kaplan Meier Weigher on right censored data. The application is carried out on the problem of regression of the length of marriage time until divorce, which is modeled with several independent variables such as the difference in the age of the couple and the number of children. The dependent variable is the length of mating time, which is the right censored data. The data that will be used is obtained from the case file of the Bandung City Religious Court in December 2021. The results of linear regression modeling with kaplan-Meier weighing have a model time until divorced = 4,34 – 0,126 (Age difference) + 5,52 (number of children) .The value of R2 is 37,64% and the MSE is 48,29501. Dependent number of children is significant to length of marriage time, in otherwise the difference in age is not significant. Abstrak. Metode untuk mengestimasi parameter pada regresi linear adalah dengan menggunakan Ordinary Least Square (OLS). Tetapi penggunaan regresi linear terbatas ketika variabel tak bebas bersifat kontinu dan seluruh data merupakan data teramati lengkap. Oleh karena itu kurang tepat apabila meneliti fenomena yang mengandung data tersensor. Metode Weighted Least Square dengan penimbang Kaplan Meier dan Synthetic Data Transformation merupakan solusi untuk menaksir parameter regresi linear pada kasus variabel tak bebasnya terdapat data tersensor. Pada skripsi ini akan membahas mengenai metode Weighted Least Square dengan Penimbang Kaplan Meier pada data tersensor kanan. Penerapan dilakukan pada masalah regresi lamanya waktu perkawinan sampai dengan bercerai yang dimodelkan dengan beberapa variabel bebas seperti selisih usia pasangan dan jumlah anak. Variabel tak bebasnya ialah lamanya waktu perkawinan yang merupakan data tersensor kanan. Data yang akan digunakan adalah data yang diperoleh dari berkas perkara Pengadilan Agama Kota Bandung pada Bulan Desember Tahun 2021. Hasil pemodelan regresi linier dengan penimbang Kaplan Meier memiliki model Waktu sampai perceraian = 4,34 – 0,126 (Selisih Usia) + 5,52 (Jumlah Anak). Variabel bebas jumlah anak signifikan terhadap lama perkawinan sedangkan selisih usia tidak signifikan.